British Association of Critical Care Nurses: Evidence‐based consensus paper for oral care within adult critical care units. Issue 4 (29th October 2020) - Collins, Tim; Plowright, Catherine; Gibson, Vanessa; Stayt, Louise; Clarke, Sarah; Caisley, Jo; Watkins, Claire Harcourt; Hodges, Emily; Leaver, Gillian; Leyland, Sarah; McCready, Patricia; Millin, Sara; et al.
Abstract: Background: Patients who are critically ill are at increased risk of hospital acquired pneumonia and ventilator associated pneumonia. Effective evidence based oral care may reduce the incidence of such iatrogenic infection. Aim: To provide an evidence‐based British Association of Critical Care Nurses endorsed consensus paper for best practice relating to implementing oral care, with the intention of promoting patient comfort and reducing hospital acquired pneumonia and ventilator associated pneumonia in critically ill patients. Design: A nominal group technique was adopted. A consensus committee of adult critical care nursing experts from the United Kingdom met in 2018 to evaluate and review the literature relating to oral care, its application in reducing pneumonia in critically ill adults and to make recommendations for practice. An elected national board member for the British Association of Critical Care Nurses chaired the round table discussion. Methods: The committee focused on 5 aspects of oral care practice relating to critically ill adult patients. The evidence was evaluated for each practice within the context of reducing pneumonia in the mechanically ventilated patient or pneumonia in the non‐ventilated patient. The five practices included the frequency for oral care; tools for oral care; oral care technique; solutions used and oral care in the non‐ventilated patient who is critically ill and is at risk of aspiration. The group searched the best available evidence and evaluated this using the Grading of Recommendations Assessment, Development, and Evaluation system to assess the quality of evidence from high to very low, and to formulate recommendations as strong, moderate, weak, or best practice consensus statement when applicable. Results: The consensus group generated recommendations, delineating an approach to best practice for oral care in critically ill adult patients. Recommendations included guidance for frequency and procedure for oral assessment, toothbrushing, and moisturising the mouth. Evidence on the use of chlorhexidine is not consistent and caution is advised with its routine use. Conclusion: Oral care is an important part of the care of critically ill patients, both ventilated and non‐ventilated. An effective oral care programme reduces the incidence of pneumonia and promotes patient comfort. Relevance to Clinical practice: Effective oral care is integral to safe patient care in critical care.